Wrist flexion rehabilitation device using arm mbed microcontroller for post-stroke patient - Chee Weng, Yap; Jumadi, Nur Anida (Penerbit Uthm, 2019)
Rehabilitation is a process of recovery of an individual from disabling or functionally limiting condition, whether temporary or irreversible, participates to regain maximal function, independence, and restoration [1]. The purpose of rehabilitation is to prevent and slow down the loss of function of the body, improve and restore the function, compensation for the lost function, and maintenance of the current function.